Properties of Young Guapuruvu (Schizolobium parahyba) Wood from a Forest Recovery Area - Athanazio-Heliodoro, Julia Carolina [UNESP]; Pacheco, Luana [UNESP]; Gaiad, Natalia; Lara-Palma, Hernando Alphonso [UNESP]; Ballarin, Adriano Wagner [UNESP] (Univ Federal Rural Rio De Janeiro, Inst Florestas, 2018)
Guapuruvu is one of the fastest growing Atlantic Forest species. It is also considered one of most important species in forest recovery areas, starting to compete with other individuals during the second stage of succession, as well as showing a capacity to be harvested and processed at this stage, after fulfilling its function as a pioneer. There are no conclusive studies about the technological potential of the wood from the young guapuruvu trees characteristic of this context. The present study evaluated the physical-mechanical properties and quality of guapuruvu wood from young trees (15 years old) from forest recovery areas in accordance with NBR 7190. The presence of tension wood did not influence the homogeneity of the wood, which is classified as strength class C20 - hardwood, with characteristic strength of 21.47 MPa in compression parallel to the grain, characteristic tension strength of 23.12 MPa parallel to grain and modulus of elasticity (MOE) of 5,925 MPa. Basic and apparent densities were 290 kg/m(3) and 336 kg/m(3) respectively. However, its low density did not lead to low mechanical strength. The high ratio between the values of its mechanical properties and apparent density, added to its high homogeneity - despite the presence of tension wood - demonstrated the good quality of its wood.
Keywords: mechanical properties; Schizolobium parahyba; wood quality